Nilai Spiritualitas Tidur dalam Hadis dan Implikasinya terhadap Manajemen Kesehatan Mental Muslim - Silvia, Kiranti (Yayasan Albahriah Jamiah Indonesia, 2025)
Sleep is a biological need with a spiritual dimension in Islam, especially when performed according to the Prophet’s guidance, thus becoming a form of worship. The increasing phenomenon of mental health disorders among Muslims demands an alternative approach that is not only medical but also based on Islamic spirituality. This study aims to examine the spiritual dimension of sleep in the Prophet’s hadith and its implications for Muslim mental health management. The research method used was a qualitative one with a thematic analysis approach to authentic hadiths containing the Prophet’s teachings regarding sleep, with selection criteria including relevance to sleep practices, prayer content, and healthy lifestyles. The analysis process was carried out through the stages of identifying hadith texts, categorizing themes, and interpreting spiritual meanings. The results show that sleep, from the hadith perspective, is not only seen as fulfilling physical needs but also as a means of spiritual submission to God. Five main indicators of sleep spirituality were identified: the intention to sleep as worship, remembrance, and prayer before bed, sleeping position according to the Sunnah, self-reflection before bed, and balancing sleep time with worship. These five indicators contribute to building inner peace, reducing anxiety, improving sleep patterns, and enhancing the quality of spiritual relationships with God. In conclusion, hadith-based sleep spirituality offers a holistic and applicable approach to Muslim mental health management, while enriching the body of hadith studies with relevant psychospiritual dimensions to address contemporary challenges.